Highly Ordered Dual Porosity Mesoporous Cobalt Oxide for Sodium‐Ion Batteries. Issue 3 (30th November 2015) - Yang, Jianping; Zhou, Tengfei; Zhu, Rui; Chen, Xinqi; Guo, Zaiping; Fan, Jianwei; Liu, Hua Kun; Zhang, Wei‐Xian
Abstract : Highly ordered mesoporous cobalt oxide (m‐Co3 O4 ) has been synthesized and applied as an electroactive material in sodium‐ion battery anodes. Mesoporous silica was used as the template for the generation of dual porosity cobalt oxide with spherical mesopores and porous nanochannels. The most notable feature of our dual porosity mesoporous Co3 O4 is that the highly ordered structure can provide much better transport pathways than the reference bulk Co3 O4 derived nanostructure, because it can facilitate the mass transport of electrolyte in the larger pores and sodium ion diffusion in the smaller pores, and also provide a large electrode–electrolyte interface for electrolyte adsorption due to the surface disorder of the Co3 O4 . The outstanding dual porosity mesopores in the cobalt oxide allow better transport pathways and thus lead to an initial capacity of 707 mA h g −1 at a current density of 90 mA g −1, retaining a capacity of 416 mA h g −1 after 100 cycles. The sodium uptake/extraction is confirmed to take place through a reversible conversion reaction, based on ex situ characterization techniques, which identify dual porosity mesoporous Co3 O4 as a high‐performance sodium‐ion battery anode material. Abstract : Highly ordered mesoporous cobalt oxide microspheres with dual porous nanochannels and high surface area are fabricated through an effective nanocasting route for sodium ion battery anodes. The sodium uptake/extraction is confirmed to take place through a reversible conversion reaction, based on ex situ characterization techniques, which identify a high‐performance sodium‐ion battery anode material.